A novel HLA‐B allele, HLA‐B*58:66. Issue 3 (September 2015) - Zhu, X.; Yang, T.; Tan, R.; Su, P.; Luo, Z.; Gao, H.
<x xml:space="preserve">Abstract</x> HLA‐B*58:66 differs from B*58:01:01 by a single‐synonymous nucleotide at position 685 where G → T (codon 205 GCC → TCC, Ala>Ser).